Roadmap for Innovative Finance for Climate Smart Agri-Food Sector in Mali - Dembélé, Daouda Sory; Derenoncourt, Marie Ena; Grosjean, Godefroy (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This report analyizes the constraints and gaps faced by women actors in three key value chains rice, onions and potatos. It reviews the available innovative financing instruments in Mali. It identifies potential investments that can attract private capital for scaling CSA and realize greater impact.